2021
DOI: 10.1515/pac-2020-1009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the possibility and molecular mechanism of carbon dioxide consumption in the Diels-Alder processes

Abstract: The large and significant increase in carbon dioxide concentration in the Earth’s atmosphere is a serious problem for humanity. The amount of CO2 is increasing steadily which causes a harmful greenhouse effect that damages the Earth’s climate. Therefore, one of the current trends in modern chemistry and chemical technology are issues related to its utilization. This work includes the analysis of the possibility of chemical consumption of CO2 in Diels-Alder processes under non-catalytic and catalytic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…In particular, for both MCA and MCB, the C3–C4 distances were 3.82 Å, whereas the C5-O1 distances were about 2.7 Å. Thus, the interatomic distances were beyond the typical range for the corresponding distances at transition states [ 36 , 37 , 38 , 39 , 40 ]. It should be underlined that these MC s did not exhibit the nature of electron density transfer complexes [ 41 ].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, for both MCA and MCB, the C3–C4 distances were 3.82 Å, whereas the C5-O1 distances were about 2.7 Å. Thus, the interatomic distances were beyond the typical range for the corresponding distances at transition states [ 36 , 37 , 38 , 39 , 40 ]. It should be underlined that these MC s did not exhibit the nature of electron density transfer complexes [ 41 ].…”
Section: Resultsmentioning
confidence: 97%
“…This analysis was performed based on CDFT reactivity indices ( Table 1 ) [ 34 ]. A similar approach was recently used to explain the course of many different types of cycloaddition processes [ 35 , 36 , 37 , 38 ]. It was found that nitrones 1 exhibited a moderately electrophilic nature.…”
Section: Resultsmentioning
confidence: 99%
“…The regioselectivity of polar processes of non-symmetric reagents can be specified through interaction between the most electrophilic center of the electrophile and the most nucleophilic ones of the nucleophile. For this purpose, electrophilic P k + and nucleophilic P k − Parr functions, derived from the changes of spin electron density reached via the GEDT process from the nucleophile to the electrophile, can be used as a powerful tool in the study of the local reactivity [42][43][44]. According to the nucleophilic P k − Parr functions of nitrylimine components 1a,c,e and the electrophilic P k + Parr functions of nitroethanes 2a-c in order to characterize the most nucleophilic and electrophilic centers of the species involved in this polar 32CA reaction were analyzed (Figure 1).…”
Section: Local Reactivitymentioning
confidence: 99%
“…Even with a relatively active nucleophile, which is cyclopentadiene 1, it does not undergo the cycloaddition reaction. DFT calculations have shown that, in the gas phase, such a process would be carried out according to a one-step mechanism, through a transition state of relatively high synchronicity (Scheme 25) [87]. However, the energy of this transition state is so high that it excludes the likelihood of effective conversion of the reaction components under normal conditions.…”
Section: Hetero Diels-alder Reactions Involving Heteroanalogs Of Dienophilesmentioning
confidence: 99%